War, conflict and human rights : theory and practice - Sriram, Chandra Lekha, 1971-; Martin-Ortega, Olga; Herman, Johanna (London : Routledge, 2014)
"War, Conflict and Human Rights is an innovative, interdisciplinary textbook combining aspects of law, politics, and conflict analysis to examine the relationship between human rights and armed conflict. This second edition has been revised and updated, making use of both theoretical and practical approaches. Over the course of the book, the authors: - examine the tensions and complementarities between protection of human rights and resolution of conflict, including the competing political demands and the challenges posed by internal armed conflict; - analyse the different obligations and legal regimes applicable to state and non-state actors, including non-state armed groups, multinational corporations and private military and security companies; - explore the scope and effects of human rights violations in contemporary armed conflicts, such as those in Sierra Leone, Sudan, the Democratic Republic of Congo, the former Yugoslavia, and Cambodia, and reflect on recent events of the "Arab Spring"; - assess the legal and institutional accountability mechanisms developed in the wake of armed conflict to punish violations of human rights law, and international humanitarian law such as the ad hoc tribunals for the former Yugoslavia and Rwanda, and the International Criminal Court, as well as other mechanisms of transitional justice; - discuss continuing and emergent global trends and challenges in the fields of human rights and conflict analysis. This volume will be essential reading for students of war and conflict studies, human rights, and international humanitarian law, and highly recommended for students of conflict resolution, peacebuilding, international security and international relations, generally"--
Includes bibliographical references and index.
Keywords: War; Human rights -- Case studies; Peace-building -- Case studies